PERAKITAN GREEN WALL DALAM RANGKA IMPLEMENTASI URBAN FARMING DI PONDOK PEKAYON INDAH KOTA BEKASI - Esi Asyani Listyowati; Nana Danapriatna; Ridwan Lutfiadi; Ahya Kamilah; Is Zunaini Nursinah; Ismarani Ismarani; M. Ikhawan Rahmanto; Dawud Ardisela; Lubna Afifah Azra (DEVOSI, 2023)
The rapid development of settlements, industry and infrastructure in the city of Bekasi has resulted in increased pollution, reduced the amount of agricultural land used as a food producer and a source of oxygen. To minimize this impact, it is necessary to have community service in the form of urban farming activities using the green wall method. The method of implementation is in the form of outreach and training, such as (1) Providing knowledge and understanding regarding urban farming and procedures for making green walls, (2) Carrying out green wall making practices. The results of its activities are the presentation of the extension material which includes the history of green walls in the world, types of green wall, the main structure of green wall, green wall containers, green wall planting media, types of plants for green wall, watering techniques on green walls, the concept of laying out green wall, and practice of making green wall (tools and materials, as well as work steps). Furthermore, the practice of making green wall (done outdoors). At the practical stage, the community is invited to be directly involved in assembling materials and arranging plants on the media so that a green wall is formed. This green wall creation program is very useful, gives satisfaction, and the program can be continued independently by partners.